2D and 3D Scans of Granular Rock Material Heaps and Calibration Models - Mario Klanfar; Tomislav Korman; Dubravko Domitrović; Vjekoslav Herceg (Scientific Data)
Abstract The angle of repose (AoR) is critical for studying granular materials in mining, geotechnical engineering, pharmaceuticals, and agriculture. Accurate AoR measurements are essential for understanding material stability and movement. The descriptor includes photographs of 86 heaps of rock materials dolomite, quartz sand, marble, and gravel. In addition, photographs of 1 ideal cone and 4 CAD drawing models are provided. These images are processed using specialized software to create detailed 2D and 3D models of the heaps. The generated STL and point-cloud models can be used to calculate the AoR with high accuracy, taking into account the complex surface morphology that traditional methods may overlook. Additionally, these models enable standardized comparisons and can be used for calibration purposes. This data facilitates the development and validation of new AoR measurement methods, enhancing the reliability and consistency of granular material analysis.